Perceptions of Educators of Reading Literacy; A Case Study of the Intermediate Phase in South African Primary Schools - Naidoo, U.; ., K. Reddy (Journal of Economics and Behavioral Studies, 2012)
The achievement of worldwide participation in education is essentially determined by the quality of education available. How well learners are instructed and how much they learn determines how regularly learners attend schools. Sound education is further affected by the following factors: time spent learning by learners, assessment methods for monitoring learner progress, styles of teaching, education spending, the language of instruction, and classroom organisation strategies (EFA Global Monitoring Report, 2005). However, the development of learners’ literacy in South Africa as a developing country is accentuated by several challenges. Many learners in South Africa have difficulty understanding the language in which they are taught which is English, as they are not taught in their mother tongue. However, the language of instruction is not solely responsible for the poor performance in international reading tests and schooling in general. Learners are also faced with socio-economic issues, very little or hardly any parental supervision and educators are faced with the challenge of finding reading methods and strategies suitable to improving reading. Learners in the foundation phase are explicitly taught reading skills. In the intermediate phase, learners are expected to apply the skills acquired in the foundation phase to access the curriculum. In reality, this is difficult to achieve. The purpose of this article is to determine educator perceptions of reading literacy in the intermediate phase with the aim of enhancing reading literacy in the intermediate phase.